2005
DOI: 10.1124/jpet.105.088252
|View full text |Cite
|
Sign up to set email alerts
|

MEN16132, a Novel Potent and Selective Nonpeptide Kinin B2Receptor Antagonist: In Vivo Activity on Bradykinin-Induced Bronchoconstriction and Nasal Mucosa Microvascular Leakage in Anesthetized Guinea Pigs

Abstract: We have tested the activity of 4-(S)-amino-5-(4-[4-[2,4-dichloro-3-(2,4-dimethyl-8-quinolyloxymethyl)phenylsulfonamido]-tetrahydro-2H-4-pyranylcarbonyl] piperazino)-5-oxopentyl](trimethyl)ammonium chloride hydrochloride (MEN16132), a novel nonpeptide kinin B(2) receptor antagonist, on bradykinin (BK)-induced inflammatory responses, bronchoconstriction, and hypotension in guinea pigs. After i.v. (1-10 nmol/kg i.v.), intratracheal (i.t.) (10-100 nmol/kg i.t.), or aerosol (0.01-0.1 mM/5 min) administration, MEN16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Icatibant (10 M inhalation exposure), however, had no effect. These results are similar to those by Valenti et al (2005), who have shown that MEN16132 is more potent and longer lasting than icatibant in inhibiting bradykinin-induced bronchoconstriction and microvascular leakage in anesthetized guinea pigs. Our result differs from those of Wirth et al (1993), however, who found that both aerosolized and intravenous icatibant inhibited the bronchoconstriction to bradykinin in anesthetized guinea pigs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Icatibant (10 M inhalation exposure), however, had no effect. These results are similar to those by Valenti et al (2005), who have shown that MEN16132 is more potent and longer lasting than icatibant in inhibiting bradykinin-induced bronchoconstriction and microvascular leakage in anesthetized guinea pigs. Our result differs from those of Wirth et al (1993), however, who found that both aerosolized and intravenous icatibant inhibited the bronchoconstriction to bradykinin in anesthetized guinea pigs.…”
Section: Discussionsupporting
confidence: 81%
“…To date, the effects of bradykinin on the airways have been largely examined after intravenous administration, inhalation, or intratracheal administration to anesthetized animals, such as guinea pigs (Ichinose and Barnes, 1990a,b;Wirth et al, 1993;Miura et al, 1994;Sakamoto et al, 1994;Valenti et al, 2005) and rats (Ellis et al, 2004). One study showed that intravenously administered bradykinin caused bronchoconstriction in unanaesthetized guinea pigs (Chodimella et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to investigate the efficacy of the novel potent and selective nonpeptide kinin B 2 receptor antagonist MEN16132 (Cucchi et al, 2005;Valenti et al, 2005) in reducing MIA-induced osteoarthritic pain in the knee joint compared with the peptide B 2 receptor antagonist icatibant.…”
mentioning
confidence: 99%